Analisis Faktor Permasalahan Kegiatan Operasional Dengan Metode FMEA di PT Indonesia Kendaraan Terminal - Abdhul Ghani, Zaki; Najwa, Alivia; Mutaqin, Yosi; Ma’ruf; Yusuf, Risandi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Indonesia Port Car Corporation (IPCC) is a company operating in the field of vehicle terminal services which specifically provides stevedoring, cargodoring, receiving and delivery services. In the era of globalization and increasing competition between companies in the logistics and transportation sector, Indonesia Port Car Corporation (IPCC) must provide services and increase quality efficiency in operational activities at port. Operational are the overall work process and implementation to management in the company. In this research, want to be focus on the problem of that have the highest FMEA scores on operational activities at Indonesia Port Car Corporation (IPCC). The method and tools use FMEA and Fishbone, the result of the tools and method show the problems of operational activities are about stockpiling yard capacity, density of activities in the field, limited land availability, limited ship berthing facilities, berthing queues, and dwelling time exceeding 7 days are the most significant factors. It is hoped that these results can help companies identify and overcome problems that disrupt operational activities, as well as improve the efficiency and quality of services provided.